Climbing back : an analysis of the summary instalment order : the New Zealand consumer-debtor repayment program : a thesis presented in partial fulfilment of the requirements for the degree of Masterate of Applied Economics at Massey University - Redhead, Kathryn A (Massey University, 1997)
The Summary Instalment Order (SIO) court-administered repayment plan was introduced as an experimental response to the problem of overcommitment. Three decades after its institution, this research forms a profile of its applicants, suggests reasons for their financial difficulty, and conducts the first evaluation of this experimental program. Comparing the profile of the SIO sample with the general population, SIO applicants are younger, have larger families, are more likely to be separated or divorced, and are more likely to reside in rented accommodation. SIO applicants are also mostly beneficiaries or in unskilled employment. Correspondingly, they have lower income and assets compared to the general population. In addition, they are more committed in terms of indebtedness, though less committed in regard to outgoing. Overcommitment is the reason for SIO application, and inadequate income, current consumption preference, and the occurrence of an unanticipated event provides explanation for overcommitment. In SIO applications, evidence of inadequate income, current consumption preference, and the occurrence of an unanticipated event suggests these have contributed to the overcommitment of SIO applicants. The SIO was intended to interrupt an indebted individual's passage to bankruptcy and to provide applicants with rehabilitation and a fresh start. Tracing applicants against the National Insolvency Database, 10.8% of applicants continued to bankruptcy in the 4-6 years following their SIO application. Analysis of the demographic and financial profile of applicants continuing to bankruptcy reveals the SIO may not have failed in any particular way. When analyzing reasons for bankruptcy application, however, SIO failure is more apparent. In addition, the high dropout rate, refile, and evidence of applicants unable to repay their debt within the three year term reinforces SIO failure. Denial of the SIO, inadequate income, current consumption preference, and the occurrence of an unanticipated event are reasons for SIO failure. Recommendations of: acceptance based upon ability to service debt, improved screening, investigation into compulsory budgeting assistance, and informing applicants regarding repayment progress and costs associated with bankruptcy application, are among suggestions outlined to combat causes of SIO failure. In addition, increased accessibility to the SIO and continued monitoring of the program's effectiveness is recommended.
Keywords: New Zealand; Debtor and creditor; Finance, Personal